Architect's guide to NEC4 - Forward, Frances (RIBA Publishing, 2018)
This user friendly guide introduces, explains, and demystifies the NEC4 contract on a practical, work-based level. Made for architects by an architect, it explores the best approach to collaborative and contractual partnering work practices. Alongside explanations of the contracts and clauses, it presents the key areas of distinction from alternative standard form contracts and examines the integrated project management principles that bring the NEC4 contracts together as a whole. It's the perfect companion book for professionals who are new to the NEC contract family and former users trying to understand the latest updates.